"Relaciòn intermedia entre el arte y la educaciòn" - Rogel Cuero, Bryan Alfredo (Machala, 2022)
Expressionism In my theme of art and education I want to emphasize based on expressionism, which is a movement that attracts my attention due to its lines and strong and intense colors. It emerged in Germany during the 20th century, where it had a large number of fields. such as: plastic arts, literature, cinema, music, theater. His first intervention was in the field of painting, coinciding with the appearance of the French Fauvist movement. Expressionism As a student, I understand it as the deformation of the reality of the figures to subjectively express nature and the human being, giving scoop to the expression of feelings as such in itself is what we feel and through a work we represent. The painting itself has the purpose of projecting a very close message in its composition, in my proposal that I am going to make it is made up of a canvas measuring 100x100 cm where the social problem is represented, capturing the positive and negative of art and education as an aid to the development of skills of children and young people to improve their academic learning. With its strong, intense colors and thick, marked strokes and its theme of loneliness and misery, Expressionism reflected the bitterness that pervaded artistic and intellectual circles in pre-war Germany. In my work, guided by photographs and videos, I want to resemble the existing relationship between art and education, since I feel that both go hand in hand and are very important for our academic training and in the future at work, also with the help of teachers. and effort of oneself when executing the work step by step, the process that we have to carry out will be of benefit to be able to organize our artistic space since as children and young people we have a promising future. In itself, this movement helps me to express what I want to represent in my work, at first it was a little difficult for me, but with help, the result to be obtained as such can be achieved, I hope I can make it.
En mi tema del arte y la educación quiero hacer hincapié en base al expresionismo que es un movimiento que me llama mucho la atención por sus trazos y colores fuertes e intensos este surgió en Alemania durante el siglo XX, en donde tuvo un gran numero de campos como: artes plásticas, literatura, cine, música, teatro etc.
Keywords: ARTE; SOCIEDAD; NIÑOS; JOVENES; EXPRESIONISMO; EMOCIONES; HABILIDADES.